2012
DOI: 10.1007/s00705-012-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239

Abstract: CD4(+)CD25(high) regulatory T cells (Treg), which are a specialized subset of T cells, play an important role in the prevention of autoimmune diseases, maintenance of immune system homeostasis and tolerance to self-antigens. Chinese rhesus macaques (CRMs) are widely used in preclinical research on potential therapeutic drugs, vaccines and mechanisms of human diseases. However, the basic immunological characterization of Treg cells of CRMs has not been well established. To characterize Treg cells, peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similar to HIV infection, the exact mechanism of regulatory T cells function as well as its frequency during Simian Immunodeficiency Virus (SIV) infection is unclear. Li et al [ 51 ] observed a higher absolute and relative number of Treg cells in Chinese Rhesus macaques in the early stages after SIV infection. No alteration on Treg cells suppressive capacity after infection was described.…”
Section: The Role Of Treg Cells On Hiv Infectionmentioning
confidence: 99%
“…Similar to HIV infection, the exact mechanism of regulatory T cells function as well as its frequency during Simian Immunodeficiency Virus (SIV) infection is unclear. Li et al [ 51 ] observed a higher absolute and relative number of Treg cells in Chinese Rhesus macaques in the early stages after SIV infection. No alteration on Treg cells suppressive capacity after infection was described.…”
Section: The Role Of Treg Cells On Hiv Infectionmentioning
confidence: 99%
“…T cells associate with both non-progression and durable control of HIV replication and that virus controllers have high levels of HIV-1-specific CD8 ? T cells producing IL-2 alone or in combination with TNF-a [11,24,42,44], these results further suggest that the protective function of T cells was destroyed in the ID group monkeys. Although it is not known whether the cells that secrete a single cytokine or several cytokines have other functions, these results suggest that abnormality of these functional subsets may be associated with the death of infected monkeys.…”
Section: Discussionmentioning
confidence: 74%
“…SHIV89.6 provirus was quantified by measuring SHIV89.6 gag levels in 500 ng of total DNA using Premix Ex Taq (Takara, Dalian, China). Plasmid pGEM-4Z-SIV gag357, described by Li et al, was used as standard template [24], diluted in nuclease-free water, ranging from 0.01 to 10 9 10 6 copies/vial/10 ll. The limit of detection by PCR was 0.1 copy/well/10 ll.…”
Section: Quantitative Pcr For Plasma Viral Load and Proviral Loadmentioning
confidence: 99%